Harmoni Antar Umat Beragama di Banten: Tinjauan Terhadap Kehidupan Masyarakat di Sekitar Gua Maria Bukit Kanada, Rangkasbitung Lebak-Banten - Dian Auliani; Angga Pusaka Hidayat (EL-FIKR: Jurnal Aqidah dan Filsafat Islam, 2023)
Lebak is one of the multicultural regencies in Banten, just like in religion. In Lebak, many adherents of different faiths exist, but inter-religious harmony is maintained, and minimal conflict exists. One example is in the Jatimulya area, Rangkasbitung, Lebak, Banten. In the Lebak district, the majority of the population embraces Islam. But in Jatimulya, there is a place of pilgrimage for Catholics, namely Gua Maria Bukit Kanada, which is currently being used as a tourist destination. Many people visit every Catholic holiday celebration, Maria Bukit Kanada Cave; even people from outside Lebak come to Maria Bukit Kanada Cave. So far, there have been no conflicts between the people of Lebak Regency, Muslims, and the Catholic community or visitors to Maria Bukit Kanada Cave. This research aims to discover how the practice of acceptance is carried out by the Muslim community in the Lebak district, especially the Jatimulya area, to maintain inter-religious harmony and how Catholics do it to be accepted in a Muslim-majority environment. The method used is descriptive qualitative with data collection techniques through literature review. Based on the research results, inter-religious harmony in the Jatimulya, Rangkasbitung, and Lebak areas was caused by the community believing in their religion and respecting other people's religions. In addition, three things can be used as indicators of inter-religious harmony: tolerance, equality, and cooperation. And, of course, the inter-religious harmony policy issued by the Regional Government also contributes to maintaining inter-religious harmony.